Saturated pool boiling heat transfer of HFE-7100 on sintered copper powder and wire mesh microporous surfaces: A comparison study. (5th November 2022) - Jiang, Yawen; Zhou, Guohui; Zhou, Jingzhi; Zhou, Feng; Huai, Xiulan
Highlights: Boiling performance on different sintered microporous surfaces was studied. Effects of effective pore size on boiling performance were examined. Bubble dynamics of boiling heat transfer on microporous surfaces were observed. A critical heat flux prediction model of microporous surfaces was made. A maximum heat transfer coefficient of 2.2 W / ( c m 2 · K ) was attained. Abstract: Pool boiling heat transfer enhancement is of great significance for the thermal management of high-heat-flux electronics. In this paper, two types of microporous coating surfaces, including sintered spherical copper powder and wire mesh microporous surfaces, were fabricated, and a comparison study on the boiling performance was experimentally conducted in saturated HFE-7100 dielectric fluid in order to further evaluate the performance difference and reveal the main mechanisms affecting the variation trend. The results showed that aided by the increased nucleation sites and capillary force, the boiling heat transfer performance of the sintered microporous coating surfaces was remarkably higher than the polished copper surface. Among them, sintered 300 in. −1 wire mesh surface demonstrated the best performance which presented an outstanding critical heat flux of 48.95 W/cm 2 with a corresponding heat transfer coefficient of 2.2 W/cm 2 ·K, increasing by up to 81.50 % and 144.44 % compared to the polished copper surface, respectively. Additionally, for the two different microporous surfaces, the heat transfer coefficient of sintered copper powder surface was slightly better at low heat fluxes. On the contrary, the sintered wire mesh surface exhibited a higher critical heat flux and a heat transfer coefficient at high heat fluxes. Finally, the experimental results were agreed well with those obtained from the critical heat flux prediction model, which provides a possible analytical model to evaluate the boiling performance of microporous surfaces.